Isothermal Aging Of Sn-3.0ag-0.5cu And Sn100c Solder Alloys Processed Via Equal Channel Angular Pressing - Baser, Muhammad Fadlin Hazim (2020)
Producing fine grains structure in metals and alloys by equal-channel angular pressing (ECAP) has become an interesting alternative since the introduction of severe plastic deformation processes. ECAP is a deformation process that imposed very large plastic strain to the bulk metal in order to make fine grained metal which could potentially improve the reliability of solder joint. High strength solder with improved joint performance and could safely be used at higher temperatures is gaining a lot of benefits, especially for electronic devices in automotive industries or aerospace applications. This study focuses on the mechanical properties of ECAPed Sn-3.0Ag-0.5Cu (SAC305) and ECAPed Sn-0.7Cu-0.05Ni-0.05Ge (patented as SN100C) under different aging time. A study was done to obtain a suitable number of ECAP pass to give the highest hardness. The result shows that 1 pass is sufficient to give the highest hardness after an increase of 5.3% (from 15.03 to 15.87) and 8.9% (from 10.77 to 11.83) for SAC305 and SN100C solder respectively. Isothermal aging was conducted for 0, 10, 50 and 100 hours at a temperature of 180°C. The resulting microstructure (thickness and morphology) was observed by table-top Scanning Electron Microscope (SEM) and Optical Microscope (OM). According to the results, the ECAPed solder displayed lower interfacial IMC thickness which is reduced by 8.5% and 11.6% for SAC305 and SN100C respectively compared to as-cast solder. However, the interfacial IMC thickness for both solders increased with prolonged aging time. The wettability of SAC305 and SN100C solder after ECAP process has improved by 14.2 % and 7.9 % respectively compared to that of the as-cast solders. It is also noticed that the wetting angle of ECAPed SAC305 solder is reduced down to 26.3o after aging for 100 hours. On the other hand, the wetting angle of ECAPed SN100C solder seems to maintain its value within the range of 33.8o to 29.3o for both solders (as-cast and ECAPed) after aging. ECAP process led to 20.4% increase in shear strength of SAC305, and both ECAPed solders slightly maintain the shear strength approximately at 44.47 MPa and 45.85 MPa respectively until aging for 50h. The improvement of ECAPed solder to the shear strength is due to the finer grains that effectively hinders the dislocation movement, but decreases with aging time due to growth of IMC layer and formation of void.